The role of adaptation to climate change in rural development - Marjainé Szerényi, Zsuzsanna; Zsóka, Ágnes; Ásványi, Katalin; Flachner, Zsuzsanna (REGIONAL AND BUSINESS STUDIES, 2011)
One of the most important consequences of global climate change is expected to be the joint appearance of extreme weather phenomena such as flood, inland inundation, and drought. Human populations living along rivers are most seriously affected by those phenomena. In the frame of the WateRisk-project (financed by the National Research and Technology Office of Hungary), we focused on the small communities living along the river Tisza, exploring the citizens’ opinions regarding the most acceptable possible solutions to water-related problems. Their conformity – also called willingness of adaptation – has been analyzed by two survey methods. Our questionnaire contained several questions on water-related issues, including the willingness of respondents to pay for increasing the proportion of natural and nature-close areas. It also examined the value system and priority setting of inhabitants towards water-related problems, local patriotism, community relationships, economic opportunities, and the natural environment, which opinions have been assessed via Q-methodology (Brown, 1996; Schmolck, 2002). With the help of Q-methodology, a value- and attitude-based behavioral profile of inhabitant groups will be shaped and their willingness and capability of adaptation will be evaluated. Keywords: climate change, rural development, willingness to pay (WTP), Q-methodology